1994
DOI: 10.1111/j.1748-1716.1994.tb09673.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic contractions in isolated small arteries of rat: role of K+ channels and the Na+, K+‐pump

Abstract: Small mesenteric arteries from Wistar rats display rhythmic tension oscillations, associated with oscillations in membrane potential, when stimulated with noradrenaline. The purpose of this study was to investigate the role of potassium conductance and Na+, K(+)-pump activity in the generation of these oscillations. The effect on the rhythmic contractions of several agents, interacting with K+ channels, was studied. Application of apamin, pinacidil or glibenclamide did not affect the rhythmic activity. Tetraet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 38 publications
(18 reference statements)
4
32
0
Order By: Relevance
“…The inability of IbTX to substitute for ChTX thus ruled out the involvement of BK Ca channels. Vasomotion persisted in the presence of TEA (10 mM) or 4-aminopyridine (4-AP; 1-5 mM) (15,17). In our system, 5 mM 4-AP did not abolish vasomotion in arteries stimulated with 10.0 M PE (n ϭ 2).…”
Section: Edhf and Sk Ca And Ik Ca Channels: Apa ϩ Chtxmentioning
confidence: 82%
“…The inability of IbTX to substitute for ChTX thus ruled out the involvement of BK Ca channels. Vasomotion persisted in the presence of TEA (10 mM) or 4-aminopyridine (4-AP; 1-5 mM) (15,17). In our system, 5 mM 4-AP did not abolish vasomotion in arteries stimulated with 10.0 M PE (n ϭ 2).…”
Section: Edhf and Sk Ca And Ik Ca Channels: Apa ϩ Chtxmentioning
confidence: 82%
“…In blood vessels ouabain increases myogenic tone (53), inhibits intercellular communication and thus vasomotion (19,28,31), and reduces the EDHF response (12). It has been suggested that inhibition of the ␣ 2 isoform is responsible for these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, studies of cultured SMCs and of pressurized cerebral arteries have demonstrated an important role for intracellular ryanodine sensitive calcium stores and potassium channels in relaxation of cerebral vessels (Nelson et al 1995;Bonev et al 1997;Gollasch et al 1998;Jaggar, 2001;Perez et al 2001). Modulation of agonist-induced vasomotion by potassium conductances has also been demonstrated in the rat mesenteric artery (Gustafsson & Nilsson, 1994). Since control of blood flow through cerebral vessels varies in several respects from that in systemic vessels (Faraci & Heistad, 1998) we were interested to investigate the role of intracellular stores in the mechanisms underlying cerebral vasomotion.…”
Section: R E Haddock and C E Hillmentioning
confidence: 99%